Beta-gamma spectroscopy of the neutron-rich 150Ba. (16th April 2018) - Yokoyama, R; Ideguchi, E; Simpson, G S; Tanaka, Mn; Nishimura, S; Doornenbal, P; Lorusso, G; Söderström, P-A; Sumikama, T; Wu, J; Xu, Z Y; Aoi, N; et al.
Abstract: Excited states in the neutron-rich nucleus ^150 Ba have been observed via β –γ spectroscopy at the Radioactive Isotope Beam Factory, RIKEN Nishina Center. The ^150 Ba ions were produced by the in-flight fission of a ^238 U beam with an energy of 345 MeV/nucleon. The E(2^+) energy of ^150 Ba was identified at 100 keV, which is the lowest known in the neutron-rich Ba isotopes. A γ -ray peak was also observed at 597 keV. A mean-field calculation with a fully 3D real space was performed and a static octupole deformation was obtained for the Ba isotopes. K^π=0^- and 1^- excited states with significant octupole collectivity were newly predicted at around or lower than 1 MeV on the ground state of ^150 Ba by a random-phase approximation calculation. The 597 keV γ ray can be interpreted as a negative-parity state, showing that ^150 Ba may possess octupole collectivity.